2023
DOI: 10.1002/ase.2309
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body donation and attitudes toward death and altruism in Changsha City in China

Abstract: In recent years, China has been facing a shortage of cadavers for teaching medical students. A better comprehension of the attitudes and factors influencing the general public's opinion toward body donation would be invaluable for planning and implementing body donation programs. Although altruistic attitude and attitudes toward death have received considerable attention in recent years globally, they have been largely understudied in China. Herein, the potential relationship between attitudes toward altruism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(60 reference statements)
0
1
0
Order By: Relevance
“… 37 Some studies have found that altruism influences the professional attitude of physicians and the establishment of harmonious doctor–patient relationships. 38 Especially in the COVID-19 pandemic, altruism is a key trait for medical personnel in the fight against it. 39 Consequently, the cultivation of altruistic beliefs and behaviours of medical students should be emphasised in medical education.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Some studies have found that altruism influences the professional attitude of physicians and the establishment of harmonious doctor–patient relationships. 38 Especially in the COVID-19 pandemic, altruism is a key trait for medical personnel in the fight against it. 39 Consequently, the cultivation of altruistic beliefs and behaviours of medical students should be emphasised in medical education.…”
Section: Discussionmentioning
confidence: 99%